A new α + β Ti-alloy with refined microstructures and enhanced mechanical properties in the as-cast state. (15th January 2022) - Zhang, Tianlong; Zhu, Jiaming; Yang, Tao; Luan, Junhua; Kong, Haojie; Liu, Weihong; Cao, Boxuan; Wu, Shiwei; Wang, Dong; Wang, Yunzhi; Liu, Chain-Tsuan
Abstract: A new (α + β) Ti-alloy, Ti-6Al-2V-1Cr-1Fe (wt%), with fine grain sizes, fine precipitates, together with the high strength and excellent ductility in its as-cast state is developed. As compared to the as-cast commercial Ti-6Al-4V alloy, the grain size and α lath thickness of the new alloy are substantially refined by 50∼75%, and the yield strength and ductility are increased by 19.7% and 51.8%, respectively. The grain size refinement is achieved by tuning the supercooling capacity of the alloy through alloying with the aid of CALPHAD calculations. In addition, the alloying of Cr and Fe substantially reduces the α lath thickness. This low-cost Ti alloy with the enhanced properties is anticipated to be highly suitable for various structural applications in its as-cast or as-printed state. Graphic abstract: Image, graphical abstract